MODELLING AND CONTROL OF RURAL PV MICRO GRID USING FUZZY LOGIC CONTROLLER - Neelima, Y.; Ashok, L.; Supraja, T.; Sushmitha, D. (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
This paper proposes an approach for the hybrid solar photovoltaic and Battery management for stand-alone applications. Battery charging process is non-linear, time-varying with a considerable time delay so it is difficult to achieve the best energy management performance by using traditional control approaches. A fuzzy control strategy for battery charging or discharging used in a renewable power generation system is analyzed in the paper. To improve the life cycle of the battery, fuzzy control manages the desired state of charge. A fuzzy logic-based controller to be used for the Battery SOC control of the designed hybrid system is proposed. This paper presents a general description of the implemented microgrid topology. The exact linearization theory adapted for power converters is applied to both a Single-Ended PrimaryInductor converter (SEPIC) to extract energy from PV modules and to a Boost converter to increase the voltage. The entire designed system is modeled and simulated using MATLAB/Simulink environment.